The effect of interval training on the anaerobic endurance capacity of a high school futsal team - Razandra Zhafran; Alex Aldha Yudi; Ikhwanul Arifan; Bram Sujadesman (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
The initial round of observations and the Running-based Anaerobic Sprint Test (RAST) have shown that members of the SMA Negeri 4 Batam futsal team have a low level of anaerobic endurance. Most players fall into the moderate category, which means their ability to keep up the intensity of performance in the second half of the games is compromised. Futsal, being a high-intensity intermittent sport, depends a lot on the anaerobic energy system, so without a good training method, it is quite a challenge to raise the players' anaerobic capacity. On the other hand, this study was developed to find out whether interval training works in boosting anaerobic endurance of the SMA Negeri 4 Batam futsal team. Experimental research was conducted quasi-experimentally. Anaerobic endurance was tested by RAST. Treatment was interval training program for 16 sessions. Using the Shapiro-Wilk normality test and paired-sample t-test at a 0.05 level of significance the data were analyzed. The current study focuses on the topic of improving the anaerobic endurance through the methods of training. The results showed that participants' anaerobic endurance significantly increased after completing the interval training program. The paired-sample t-test revealed that the value of t calculated (6.332) was greater than the critical t value (2.145), with a significance level of 0.000 (p < 0.05). The present study demonstrates that interval training substantially improves anaerobic endurance of futsal players. Thus, one can adopt interval training as a way to improve the anaerobic performance and, thereby, support the optimal match performance of very high-intensity activities in futsal.